Pengembangan Entrepreneurship pada Program MA Keterampilan melalui Inovasi Model Pembelajaran Teaching Factory di MAN 2 Kulon Progo - Imam Muttaqien (Jurnal Pendidikan Madrasah, 2019)
MA Skills is one of the programs that is common (not SMK) with the same curriculum content as Madrasah Aliyah in general (regular) plus an intracuricular program in various areas of structured skills. MA Skill has 5 majors namely agribusiness processing agricultural products (APHP), fashion design, visual communication design, audio video engineering, and food management. Skills Program Given according to the spectrum adapted from SMK. Model teaching factory began to be implemented in MAN 2 Kulon Progo aims to improve the competency of the students to be able to become a reliable businessman and work according to their competency skills. Model teaching factory has 3 components, namely: 1) product as a media to introduce competence, 2) sheets of work that contains series and work assessments in accordance with industry standard working procedures, and 3) arrange a learning schedule that Enables optimal delivery of soft skills and skill to the students. The success of the teaching factory model involved all stakeholders in the madrasah can develop entrepreneurship activities in MAN 2 Kulon Progo.